The effects of nitrate ingestion on high-intensity endurance time-trial performance: A systematic review and meta-analysis - Wong, T. H.; Sim, A.; Burns, S. B. (Journal of Exercise Science & Fitness, 2022)
Background/Objective Dietary nitrate ingestion extends endurance capacity, but data supporting endurance time-trial performance are unclear. This systematic review and meta-analysis evaluated the evidence for dietary nitrate supplementation to improve high-intensity endurance time-trial performance over 5-30 min on the premise that nitrate may alleviate peripheral fatigue over shorter durations.